Anti-inflammatory effects of alosetron mediated through 5-HT(3) receptors on experimental colitis - Motavallian, Azadeh (Res Pharm Sci, 2019)
Development of new medicine with fewer deleterious effects and more efficacies for treatment of inflammatory bowel disease is needed. 5-Hydroxytryptamine 3 receptor (5-HT(3)R) antagonists have exhibited analgesic and anti-inflammatory features in vitro and in vivo. The present study was designed to evaluate the anti-inflammatory effect of alosetron, a 5-HT(3)R antagonist, on trinitrobenzenesulfonic acid (TNBS)-induced ulcerative colitis in rats. Two h subsequent to induce colitis (intracolonic instillation of TNBS, 50 mg/kg) in male Wistar rats, alosetron (1 mg/kg), dexamethasone (1 mg/kg), meta-chlorophenylbiguanide (mCPBG, a 5-HT(3)R agonist, 5 mg/kg), or alosetron + mCPBG were administrated intraperitoneally for 6 days. Animals were thereafter sacrificed and the efficacy of drugs was evaluated macroscopically, histologically, and biochemically (myeloperoxidase, tumor necrosis factor-alpha, interleukin-6, and interleukin-1 beta) on distal colon samples. Treatment with alosetron and dexamethasone improved macroscopic and microscopic colonic damages significantly and decreased myeloperoxidase activity and colonic levels of inflammatory cytokines. The profitable effects of alosetron were antagonized by concurrent administration of mCPBG. Our data provided evidence that the protective effects of alosetron on TNBS-induced colitis can be mediated by 5- HT3R.